Cancer Care in Elderly Patients; A Record Based Retrospective Analysis of Clinical Profile and Overview of Treatment - Panikkar, Drishya S; Narayanan, Geeta S; BR, Kiran Kumar (Asian Pacific Journal of Cancer Biology, 2024)
Background: Cancer can develop at any age, but the incidence of cancer rises dramatically at a later stage in life. Cancer management in older individuals can be complex due to comorbidities and physiological age-related changes. These factors can affect how and when cancer is diagnosed, whether treatment is offered, and how well patients tolerate anticancer therapy. This retrospective study aimed to assess the clinical profiles of elderly cancer patients to optimize cancer care. Materials and Methods: This retrospective study included cancer patients who attended our oncology department between 2018 and 2022 and were 65 years and older. Data on cancer type, performance status, intent of treatment, treatment completion, and follow-up status at 3 years were documented and analyzed. Results: A total of 230 patients were included in the study. The most common malignancies were head and neck carcinoma and lung cancer, followed by esophageal and colorectal malignancies. Most patients presented with a performance status of 1 (57.8%). The intent of therapy was curative for 49.1% of patients and palliative for 30.1%. At a median follow-up of 36 months, 15% of treated patients were alive without disease and on regular follow-up. Conclusion: Head and neck cancer was the most common cancer observed in our study. Elderly cancer patients presented with a good performance status, suggesting that they deserve the same opportunities as younger patients for treatment and survival options.